Delayed Hospital Presentation and Neuroimaging in Non-surgical Spinal Cord Infarction - Pikija, Slaven; Mutzenbach, Johannes Sebastian; Kunz, Alexander B.; Nardone, Raffaele; Leis, Stefan; Deak, Ildiko; McCoy, Mark R.; Trinka, Eugen; Sellner, Johann (Frontiers in Neurology, 2017)
Background Lack of timely recognition and neuroimaging may be a barrier to reperfusion efforts in acute spinal cord infarction. Methods We performed a retrospective study of patients diagnosed with acute non-surgical spinal cord infarction at our tertiary academic center from 2001-2015. We studied parameters associated with time from symptom onset to initial hospital presentation and magnetic resonance imaging (MRI) of the spinal cord. Results We identified 39 patients among whom anterior spinal artery syndrome was the most frequent presentation (87.2%) and atherosclerosis the most common etiology (56.4%). Nearly half of the patients presented to the emergency department on the same day of symptom onset (48.7%) but only 9 (23.1%) within the first 6 hours. Average time from symptom onset to spinal cord MRI was 3.2 days. We could not identify clinical, radiological or outcome patterns associated with early vs. delayed presentation and imaging. Discussion Our study found a time lag from symptom onset to hospital presentation and spinal cord MRI in patients with acute spinal cord infarction. These findings point at low clinical suspicion of spinal cord syndromes and limited recognition as a potentially treatable medical emergency.